Cultural Symbols, Identity and Meaning Formation: Symbolic Interactionist Analysis of Chinua Achebe’s Things Fall Apart - Mehnaz (University of Chitral Journal of Linguistics and Literature, 2024)
The present paper makes an attempt to examine how George Herbert Meade’s theory explains people’s use of symbols as a sense-making tool to elucidate the socialization process, role performance, identity, and meaning formation within the Igbo society for explaining various aspects of human life in the novel Things Fall Apart. This study is significant as it deals with character analysis of Okonkwo, to see how different roles of son, warrior, husband, father and a clansman are defined in Igbo culture during various phases of family and social life to clarify how Symbolic Interactionism has given a new impetus to see society, culture, psychology and relationships. It argues that the physical setting is significant to human behavior and human actions can be interpreted with the critical analysis of cultural symbols and the way they are deployed. It concludes that human behavior is based upon assigning meanings and their symbolic interpretations of the objects that surround them. The Symbolic Interactionist analysis of the novel clearly indicates that Okonkwo’s self and meaning formation is built on perceptions of the reactions of his clansman and his self-concept functions to direct his behavior. The development of different roles changes role and behavior patterns. The internal and external happenings influence role performance, conflict, struggle, and affect the nature, attitude, and self-image of Okonkwo. Moreover, it also affirms that the cultural symbols for honor, respect, and manliness etc. are not fixed naturally rather these are the constructions of the mind and are given meaning through interaction of the people.